Modulating Properties of Piroxicam, Meloxicam and Oxicam Analogues against Macrophage-Associated Chemokines in Colorectal Cancer - Paulina Lewandowska; Izabela Szczuka; Iwona Bednarz-Misa; Berenika M. Szczęśniak-Sięga; Katarzyna Neubauer; Magdalena Mierzchała-Pasierb; Marek Zawadzki; Wojciech Witkiewicz; Małgorzata Krzystek-Korpacka (Molecules, 2021)
The mechanisms underlying the antineoplastic effects of oxicams have not been fully elucidated. We aimed to assess the effect of classic and novel oxicams on the expression/secretion of macrophage-associated chemokines (RTqPCR/Luminex xMAP) in colorectal adenocarcinoma cells, and on the expression of upstream the non-steroidal anti-inflammatory drug (NSAID)-activated genes NAG1, NFKBIA, MYD88, and RELA, as well as at the chemokine profiling in colorectal tumors. Meloxicam downregulated CCL4 9.9-fold, but otherwise the classic oxicams had a negligible/non-significant effect. Novel analogues with a thiazine ring substituted with arylpiperazine and benzoyl moieties significantly modulated chemokine expression to varying degree, upregulated NAG1 and NFKBIA, and downregulated MYD88. They inhibited CCL3 and CCL4, and their effect on CCL2 and CXCL2 depended on the dose and exposure. The propylene linker between thiazine and piperazine nitrogens and one arylpiperazine fluorine substituent characterized the most effective analogue. Only CCL19 and CXCL2 were not upregulated in tumors, nor was CXCL2 in tumor-adjacent tissue compared to normal mucosa. Compared to adjacent tissue, CCL4 and CXCL2 were upregulated, while CCL2, CCL8, and CCL19 were downregulated in tumors. Tumor CCL2 and CCL7 increased along with advancing T and CCL3, and CCL4 along with the N stage. The introduction of arylpiperazine and benzoyl moieties into the oxicam scaffold yields effective modulators of chemokine expression, which act by upregulating NAG1 and interfering with NF-κB signaling.